Macrophage-derived lipid agonists of PPAR-α as intrinsic controllers of inflammation. (2nd January 2016) - Pontis, Silvia; Ribeiro, Alison; Sasso, Oscar; Piomelli, Daniele
Abstract: Macrophages are multi-faceted phagocytic effector cells that derive from circulating monocytes and undergo differentiation in target tissues to regulate key aspects of the inflammatory process. Macrophages produce and degrade a variety of lipid mediators that stimulate or suppress pain and inflammation. Among the analgesic and anti-inflammatory lipids released from these cells are the fatty acid ethanolamides (FAEs), which produce their effects by engaging nuclear peroxisome proliferator activated receptor-α (PPAR-α). Two members of this lipid family, palmitoylethanolamide (PEA) and oleoylethanolamide (OEA), have recently emerged as important intrinsic regulators of nociception and inflammation. These substances are released from the membrane precursor, N-acylphosphatidylethanolamine (NAPE), by the action of a NAPE-specific phospholipase D (NAPE-PLD), and in macrophage are primarily deactivated by the lysosomal cysteine amidase, N-acylethanolamine acid amidase (NAAA). NAPE-PLD and NAAA regulate FAE levels, exerting a tight control over the ability of these lipid mediators to recruit PPAR-α and attenuate the inflammatory response. This review summarizes recent findings on the contribution of the FAE-PPAR-α signaling complex in inflammation, and on NAAA inhibition as a novel mechanistic approach to treat chronic inflammatory disorders.